Designing And Implementation Of Embedded Based Alert System For Overheat Detection In Machines (Journal of Pharmaceutical Negative Results, 2023)
Overheating of equipment has become a major issue in big enterprises, particularly in the petrochemical fields, throughout the years. When electrical, pneumatic, hydraulic, or electromechanical machinery, such as that used in production or treatment processes, malfunctions or begins to break down, at minimum a part of the machine's working temperature rises. This might result in a devastating breakdown at any moment. He expresses particular concern about the devices' temperature being monitored and maintained. A temperature-based, energetic material-containing actuator is chosen for action at a pre-registered temperature signaling the device's impending failure and placed in heat exchange with it. Whenever the machine achieves the pre-set temperature, the actuator indicates this by displaying a flag or providing some passively warning signal. The temperature transducer LM35 delivers the sensed data to the ATMEGA328 microcontroller, which processes it and transmits the temperature on the Liquid Crystal Display panel regularly. The LCD has a seven-segment display screen that can show up to three digits. By using four push buttons to control the maximum and minimum temperatures, the method helps to set and adjust the temperature limit. By pushing the set button, the user can increase or decrease the machine’s temperature. Based on the temperature range the alert system varies. The exceeded temperature is divided into three ranges. If the temperature is in range 1 the LED glows. Then if the temperature reaches the second level, two LED glows and the buzzer also rings. If the temperature exceeds the setpoint and reaches the third level then the two LED glows, the buzzer rings and the SMS alert will be sent to the concerned mobile number via the GSM module.